Social Movements and Popular Health Practices: contemporary challenges in the perception of protagonists from Paraíba (Emancipação, 2023)
Social movements and popular health practices have historically generated actions of care, participation, and education in health, strengthening comprehensiveness and the development of healthy and sustainable territories. This study aims to analyze the challenges faced by these movements and practices in collective public health, as perceived by key participants in experiences within the state of Paraíba, Brazil. Using a qualitative approach, 28 individuals with recognized roles in the state were interviewed, and their responses were transcribed, analyzed, and categorized. The study yielded 7 key findings: weaknesses in youth leadership; disintegration of social movements; limited political engagement; restricted institutional and governmental support; undervaluation of popular knowledge; vulnerabilities in rural movements; and a growing influence of ultraliberalism in the current political landscape. These results can inform new initiatives for the education of these movements and practices at their grassroots and foster strategies for their organizational enhancement, addressing and overcoming the identifiedgaps.
Keywords: Social Actors; Popular Education in Health; Paraiba; Social Participation in Health